THE IDEAS OF DIGITIZATION IN THE MANAGEMENT OF THE EDUCATIONAL SYSTEM, INCLUDING THE ROLE OF EGOVERNMENT, THE INCREASE IN THE QUALITY OF EDUCATION AND ITS EFFECTIVENESS, WILL BE EXPLAINED (Conference Zone, 2022)
The ideas of digitization in the management of the educational system, including the role of E-government, the increase in the quality of education and its effectiveness, will be explained